Effect of Reinforced Concrete Cracking on Chloride Ion Penetration - Yuan Chao; Li Yang; Chen Xu; Wang Wenjie (MATEC Web of Conferences, 2015)
This article is to explore the effect of conditions of reinforced concrete on chloride ion penetration. The influence of the crack width and the thickness of protective layer were studied. In consideration of the randomness of concrete crack width and the fuzziness of its effect on durability, the fuzzy reliability index calculation method was adopted in this paper to calculate the reliability of crack control criterion. Different thicknesses of protective layer of reinforced concrete specimens were designed, and cracks of reinforced concrete specimens were formed by embedding steel sheet. Then specimens were soaked in chloride solution. Finally, the content of chloride ion in concrete was determined by sampling. The results showed that cracks significantly increased diffusion speed of chloride ion within a certain region and the influence degree increased with the increase of crack width. And the influence of concrete cover thickness and concrete strength level on βw was not significant.